THE ROLE OF HATHA YOGA IN HUMAN IMMUNO DEFICIENCY VIRUS (HIV)/ACQUIRED IMMUNO DEFICIENCY SYNDROME (AIDS) - Sakthivel, *Rajathi; Shanmugam, Rajendran Shankar; Mohamed Usman, Noor; Ramaswamy, Somasekar; Rethinasabapathi, Latha (AYUSHDHARA, 2016)
The Acquired Immuno Deficiency Syndrome (AIDS) considered to be great deal of courage to face the disease that seems to have no cure as yet. Many of the people living with HIV (PLHIV), have the intense feelings of hopelessness, loneliness, fear, anxiety and depression. The Highly Active Anti Retroviral Therapy (HAART) has effectively reduced HIV related morbidity and mortality for PLHIV. Even they are living longer with ART, but significant side-effects like anorexia, nausea, vomiting, fatigue and stress related problems are unavoidable. The National Institute of Health and World Health Organization recommends that, yoga makes to minimize the side effects ART and stress related problems of PLHIV. Among many branches of yoga, Hatha yoga enhances the capacity of the physical body through the use of series body postures, movements (Asanas) and breathing techniques (Pranayama). It’s a form of mind-body fitness that involves the combination of muscular activity and an internally focus on the mind for awareness of the self, breath and energy aids to boost immunity and relax the mind. Many research studies supported that, this behavior modification of yoga is potentially safe, effective and this low-cost management help to ‘detoxify’ the body, mitigate chronic fatigue, enhance endurance, improve organ and immune functions makes to enhance overall well being and quality of life of PLHIV.